The importance of usability features in enhancing online communication satisfaction - Mohd Azul Mohamad Salleh,; Ali Salman,; Mohd Nor Shahizan Ali,; Hasrul Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Web 2.0 is providing more responsive, interactive and online platforms of participation and engagement within users in organizations. The growth of the Internet gives a significant contribution to the development of online systems. The acceptance and usage of online system in organizations depend on various key factors such as ease of use, interactivity and usability. This study evaluates the importance of usability of online information management systems (IMS) in the context of user attitudes to online communication satisfaction which drives usage. Based on a survey of 223 employees at four research universities in Malaysia, this study adapted the communication satisfaction and usability to examine the online satisfaction in using IMS. The results indicate that there is a positive and significant relationship between usability and online communication satisfaction toward IMS usage. This study reveals the importance of usability in understanding the requirements in improving communication satisfaction, especially in developing online systems.